REDEFINISI MADRASAH: MENGEMBALIKAN PRODUK HIBRIDA YANG USANG DENGAN MENAMBAHKAN UNSUR ISLAMI UNTUK MENINGKATKAN KEDALAMAN PENGETAHUAN AGAMA DAN MENINGKATKAN HASIL AKADEMIK - Ashar, Salim (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
Religious education provided in madrasas, such as the schools themselves, is a hybrid product that combines subjects taught in traditional quran schools with modern pedagogies. Character, moral, and good behavior are the heart of Islam. All Islamic knowledge is directed at improving the behavior of insiders and outsiders and their relationship with God and humanity in general. Ethics is its own science in Islam and, in fact, the most important science for all advanced fields of knowledge is morals (straight characters). The general typology used to explain the authority of Islam more generally includes the division of authority based on knowledge (exoteric); access to the spiritual (esoteric) realm. It has been established from the Prophet and his colleagues that the transmission of ethical knowledge is the aim of Islam. the results of the analysis provide an overview in the class I elementary thematic book p. 10